THE EVOLUTION OF THE “STREAM OF CONSCIOUSNESS” TECHNIQUE IN ENGLISH LITERATURE - Feruza Rasulovna Rashidova (Western European Studies, 2025)
This article analyzes the emergence and gradual development of the “stream of consciousness” technique in English literature. It demonstrates that between the late nineteenth and early twentieth centuries, this technique was shaped as an artistic and aesthetic method, as exemplified in the works of J. Joyce, V. Woolf, D. H. Lawrence, and W. Faulkner. The direct connection of the “stream of consciousness” with psychologism, interior monologue, subjective perception, and the relative interpretation of time is scientifically substantiated.
Keywords: stream of consciousness; English literature; modernism